Liquid Crystal Elastomers with Enhanced Directional Actuation to Electric Fields. Issue 43 (12th September 2021) - Fowler, Hayden E.; Rothemund, Philipp; Keplinger, Christoph; White, Timothy J.
Abstract: The integration of soft, stimuli‐responsive materials in robotic systems is a promising approach to introduce dexterous and delicate manipulation of objects. Electrical control of mechanical response offers many benefits in robotic systems including the availability of this energy input, the associated response time, magnitude of actuation, and opportunity for self‐regulation. Here, a materials chemistry is detailed to prepare liquid crystal elastomers (LCEs) with a 14:1 modulus contrast and increase in dielectric constant to enhance electromechanical deformation. The inherent modulus contrast of these LCEs (when coated with compliant electrodes) directly convert an electric field to a directional expansion of 20%. The electromechanical response of LCE actuators is observed upon application of voltage ranging from 0.5 to 6 kV. The deformation of these materials is rapid, reaching strain rates of 18% s −1 . Upon removal of the electric field, little hysteresis is observed. Patterning the spatial orientation of the nematic director of the LCEs results in a 2D–3D shape transformation to a cone 8 mm in height. Individual and sequential addressing of an array of LCE actuators is demonstrated as a haptic surface. Abstract : Stimuli‐responsive materials are compelling approaches to advance the capabilities of soft robots as artificial muscles. A material chemistry is reported to prepare liquid crystal elastomers with a fivefold increase in directional actuation response to electric fields. Electromechanical deformation of liquid crystal elastomers is shown to be rapid and locally programmable.